The role of the libraries in bridging the digital divide: a case of Rivers State University Central Library, Port Harcourt - Wagwu, Victor; Okoro , Caroline A. (Communicate: Journal of Library and Information Science, 2025)
The study examined the role of the libraries in bridging digital divide: a case of Rivers State University Central Library Port-Harcourt, Rivers State. It further examined the bridging of the digital divide gap between socio-economic and digital information resources. Three objectives and three research questions guided the study. Descriptive research design was used for the study with a population of 11 professional librarians working with Rivers State University Central Library. The study sample size was the entire population using census sampling technique method. The research instrument used for data collection was a self-structured questionnaire. The instrument was a modified 2-point rating scale of Yes and No. The data analysis was done using frequency and percentage count for the research questions. The findings of the study revealed among other things that librarians in Rivers State University Central Library is making significant efforts to provide access to digital resources on socioeconomic divide. The study concluded that libraries play an ever-more-important role in promoting equality and closing socioeconomic divides as long as they remain vital hubs for digital information and resources. To make sure that these organizations continue to be successful in closing the digital divide and empowering their communities, more study and ongoing assessment of library services are crucial. It therefore recommended among others that the library should push for a larger budgetary allocation that is dedicated to digital resources.